Advances in Internet, Data & Web Technologies The 6th International Conference on Emerging Internet, Data & Web Technologies (EIDWT-2018) - Barolli, Leonard; Xhafa, Fatos; Javaid, Nadeem; Spaho, Evjola; Kolici, Vladi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents original contributions on the theories and practices of emerging Internet, data and Web technologies and their applicability in businesses, engineering and academia, focusing on advances in the life-cycle exploitation of data generated from the digital ecosystem data technologies that create value, e.g. for businesses, toward a collective intelligence approach. The Internet has become the most proliferative platform for emerging large-scale computing paradigms. Among these, data and web technologies are two of the most prominent paradigms and are found in a variety of forms, such as data centers, cloud computing, mobile cloud, and mobile Web services. These technologies together create a digital ecosystem whose cornerstone is the data cycle, from capturing to processing, analyzing and visualizing. The investigation of various research and development issues in this digital ecosystem are made more pressing by the ever-increasing requirements of real-world applications that are based on storing and processing large amounts of data. The book is a valuable resource for researchers, software developers, practitioners and students interested in the field of data and web technologies.
Implementation of a New Function for Preventing Short Reconnection in a WLAN Triage System -- A Web-based English Listening System for Learning Different Pronunciations in Various Countries -- FOG Computing and Low Latency Context-Aware Health Monitoring in Smart Interconnected Environments -- Application of Fuzzy Logic for Improving Human Sleeping Conditions in an Ambient Intelligence Testbed -- Design and Implementation of a Hybrid Intelligent System Based on Particle Swarm Optimization and Distributed Genetic Algorithm -- Integrated Model of the Wavelet Neural Network Based on the Most Similar Interpolation.
Keywords: Computational intelligence; Telecommunication; Application software; Computational Intelligence; Communications Engineering, Networks; Computer and Information Systems Applications